Localization of Dipetalonema reconditum (GRASSI, 1890) (Nematoda filariidae) de Canis familiaris - Mello, Edson Barros Figueira de; Maia, Antonio Augusto Mendes; Mello, Leila Alcione Pinheiro de (Brazilian Journal of Veterinary Research and Animal Science, 1994)
The necropsy of 24 dogs with positive blood serum test for Dipetalonema sp microfilarias demonstrated that 93.9% of the parasites were located in the subcutaneous tissue and 6.1% in general visceral organs. The helminths were localized in different anatomical regions, the chest was found with the highest frequency.